Improving Information management in resource as a service framework using gamification technique: a case study in Institut Pendidikan Guru Malaysia - Nordin A Rahman, M; Khairi, WM; Awang, W (International Journal of Engineering and Technology, 2018)
The issue of information management is crucial for any academic institution. Convenient access to requested content is creating a competitive advantage for different types of decisions. Information management process in Institut Pendidikan Guru (IPG) often create problems because there is no systematic way of storage management. IPG lecturers stored their teaching materials in different kind of methods. This situation cause in a loss of resources, difficult to retrieve and also cannot be identified when it's needed. Dealing with large volumes of resources it is essential to use technological solutions that enable flexible storage, retrieval, processing and interpreting information. To solve the problems, this article introduced a framework that use single platform and named as Information Sharing for Learning (IS4L) for managing teaching and learning resources in IPG. The resources will be stored and can be accessed at any time. The framework also applied the technique of gamification to motivate and encourage users to use the application and consequently will increase the volume of resources stored. The developed application based on the proposed framework could help to motivate and engage peoples to share their resources and enhance quality of services in IPG. Finally it could assist to improve the performance and effectiveness of services to achieve usersâ€™ satisfaction.Â